Economics Language and Assumptions: How Theories can Become Self-Fulfilling - Ferraro, Fabrizio; Pfeffer, Jeffrey; Sutton, Robert I. (Academy of Management Review, 2005)
Social science theories can become self-fulfilling by shaping institutional designs and management practices, as well as social norms and expectations about behavior, thereby creating the behavior they predict. They also perpetuate themselves by promulgating language and assumptions that become widely used and accepted. We illustrate these ideas by considering how the language and assumptions of economics shape management practices: theories can "win" in the marketplace for ideas, independent of their empirical validity, to the extent their assumptions and language become taken for granted and normatively valued, therefore creating conditions that make them come "true."